Research on peripheral clamping of large-aperture laser transport mirror - Cao, TingFen; Liu, Bowu; Ni, Wei; Zhang, Jinli; Wang, Hui; Chen, Xiaojuan; Li, YinGang; Zhou, Hai; Jiang, Xiaodong; Hu, Dongxia; Zhu, Qihua (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
This article introduces the study of peripheral clamping for large-aperture laser mirrors in high power laser facilities. Some multi-point clamping schemes were experimentally tested, the results of the experiments show that these schemes cannot meet the technical requirements, and in the simulation analysis, we explain the reason for this phenomenon. It is concluded that the additional bending moment caused by the non-ideal process factors in the multi-point clamping is the main cause for the surface distortion. Based on the above conclusions, we carried out research on minor-point clamping. Experimental verification of the minor-point clamping were done, the results show that the minor-point clamping can meet the requirements of technical indicators in whole process. This work can provide a reference for the design of the large-aperture transport mirror clamping structure, which may be used in huge laser devices and telescopes.
Optica Applicata, Vol. 53, 2023, nr 2, s. 227-238
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; transport mirror; peripheral clamping; surface distortion; assembly structure